Peru tourism satellite accounts, year 2013 - Pazos Miranda, José (2017)
They describes the work carried out by the Observatory Tourist of Peru of the Professional School of Tourism and Hospitality of the University of San Martin de Porres, they posed as an aim to determine the wealth generated in the economic course of the museums, archaeological rests and natural sites of the regions of Arequipa, Cusco, Lambayeque and La Libertad. In addition, it arises from background relating to the investigations carried out, as well as, differences from the quantitative and qualitative point of view in the tourism sector. For the purposes of the measurement of the GDP of each of the corresponding production, units used the method of remuneration to the factors of production.